PENGARUH WAKTU DAN LUAS PERMUKAAN TERHADAP KETEBALAN PRODUK PADA ELEKTROPLATING ACID ZINC - Irman .; Budhi .; Faevi .; Iis . (Program Studi Teknik Kimia, Universitas Pamulang, 2017)
This research using Faraday’s law to analize result of measurements. There are 2 parameters varying in research, the surface area of specimen ( 6 x 10 cm², 6 x 5 cm² and 5 x 3 cm²) and time ( 6, 9 and 12 minutes). The research method was done by electroplating scheme consists of a cathode, anode, electrolyte, which is coupled with a DC electrical current that is placed on Hull Cell. The purpose of research is to determine impact of extent of time and amount of surface area of specimen to layer thickness occured from the acid zinc electroplating methods. The result of research obtained is the greater of surface area will form specimen mass and layer smaller, and the longer of electroplating process time will form speciment mass and layer increasing thickerKeywords : Electroplating, Acid Zinc